Inheritance of resistance to Stenocarpella macrospora (Earle) ear rot of maize in the midaltitude zone of Nigeria - Olatinwo, R.; Cardwell, K.; Menkir, A.; Deadman, M.L.; Julian, A. (1999)
Inheritance of resistance to Stenocarpella macrospora (Earle) Sutton (syn. Diplodia macrospora Earle) ear rot of maize was studied among selected maize populations in the mid-altitude (1280 m) agro-ecological zone of Nigeria. Diallel analysis among the populations showed significant values for general combining ability (GCA) and specific combining ability (SCA) effects at 5% and 1% levels respectively. Variance components of GCA and SCA on Stenocarpella ear rot were 0.019 and 0.627 respectively, indicating that non-additive genes play major roles in the inheritance of Stenocarpella ear rot resistance. The GCA and SCA effects were relatively dependent on the materials involved in the evaluations. Generation mean analysis was used on five selected parent inbreds (2 resistance and 3 susceptible crossed to give P1, P2, F1, BC1, BC2 and F2 generations). Estimates of the six parameters on ear rot indicate that dominance gene effects made the major contribution to variation in ear rot of maize in the crosses studied. The magnitude and significance of the estimates for digenic effects in the crosses suggest that epistatic gene effects are present and important in the basic mechanism of Stenocarpella ear rot inheritance in the populations studied. Additive effects have only minor importance in the total variation